Development of a community pharmacy-based intervention for patients with uncontrolled asthma - Claudie Turcotte; Rébecca Fénélon-Dimanche; Catherine Lemière; Marie-France Beauchesne; Bachir Abou-Atmé; Isabelle Chabot; Lucie Blais (Elsevier, 2022)
Background: Achieving asthma control is often difficult, despite the availability of effective medications. Because of their expertise, regular contact with patients, and accessibility, community pharmacists can play an important role in helping patients manage uncontrolled asthma. Objective: To develop a community pharmacy-based intervention for improving asthma control in patients with uncontrolled moderate to severe asthma. Methods: A qualitative study involving two focus groups with six and five community pharmacists, respectively, five individual interviews with community pharmacists, and three individual interviews with asthma patients was conducted using semi-structured interview guides. Focus groups aimed to develop the first prototype of the intervention and the topics included criteria to identify patients with uncontrolled asthma, content of the intervention to manage uncontrolled asthma, and potential logistical issues. Interviews were subsequently conducted with individual pharmacists and asthma patients to evaluate the prototype and finalize the intervention. The interviews and focus group transcripts were analyzed thematically, using an iterative process. Results: In focus groups and interviews, the pharmacists discussed how they screen patients with uncontrolled asthma using prescriptions refills, their needs for a convenient tool to assess asthma control, the necessity to identify causes of uncontrolled asthma to guide asthma management strategies, and the importance of patient follow-up. During interviews, patients shared their interest for the commitment of pharmacists to managing asthma. The final intervention consists of structured face-to-face counselling sessions at community pharmacies, with six steps: screening of patients with potential uncontrolled moderate to severe asthma, assessment of asthma control, identification of the causes of uncontrolled asthma, strategies for controlling asthma, an optional follow-up at the next prescription refill, and a follow-up 3 months after the initial intervention. Conclusions: The patients and community pharmacists reached consensus on the intervention's key elements and provided support for implementing the intervention in community pharmacies.